(untitled) (Vegueta: Anuario de la Facultad de Geografía e Historia, 2020)
La escisión que supuso la independencia de Portugal de España en 1640 ha supuesto, al mismo tiempo, una escisión historiográfica entre quienes hoy estudian a los portugueses en Asia y quienes se dedican a las Filipinas. Así, muchas veces, unos y otros no asumen que la guerra llevada a cabo por la Compañía Neerlandesa de las Indias Orientales (VOC) contra Manila fue parte de un conflicto más amplio contra el conjunto de los territorios de la Monarquía Hispánica en toda Asia. Este artículo pretende integrar las incursiones navales neerlandesas en Filipinas en el contexto de ese conflicto más amplio. / Portugal’s independence from Spain in 1640 has also proved cause for a correspondingly clear distinction between historians studying the Portuguese in Asia and those who study the colonial Philippines. At times, it seems that historians of both groups are not fully aware that the war waged by the Dutch East India Company (VOC) against Manila was part of a wider conflict against all of the territories of the Spanish Monarchy throughout Asia. This article aims to position the Dutch naval incursions into the Philippines within the context of this broader international conflict, comparing them with similar initiatives of the VOC against Portuguese possessions scattered throughout the East.